Enhanced light extraction efficiency of integrated LEDs devices 7with the taper holes microstructures arrays. (September 2015) - Huang, Kun; Gan, Yanchang; Wang, Qingkang; Jiang, Xuesong
Abstract: A kind of polydimethylsiloxane (PDMS) film with taper holes microstructures arrays (THMA) was fabricated and coated on the integrated LEDs device. The integrated LEDs device with THMA was then measured along with a comparative series of tests of the integrated LEDs device encapsulated flatly in the following categories: electroluminescence spectra, luminous flux, radiant flux and light extraction efficiency. The experimental results demonstrated that light extraction efficiency of integrated LEDs devices could be enhanced by THMA. Furthermore, the improvement of light extraction efficiency is up to 23.41–24.43% under different injection currents. Highlights: We propose a method of enhancing efficiency of integrated LED devices. Taper holes microstructure arrays (THMA) to enhance light extraction efficiency could be replicated from hard mold at a low cost. The method of coating film with THMA is compatible with conventional encapsulation.